Practice rate of nursing students about communication with patients, Tonekabon Shahid Rajai Hospital, 2002-03 - N Navabi (Babol University of Medical Sciences, 2003)
Background and Objective: Communication with patients paves the way for the nurses to know the patients needs. As the most important role of the nurses is training, their goal is to increase the awareness level of the patients in prevention of diseases. The aim of this study was to survey the practical activities of nursing students in clinical communication with patients. Methods: This descriptive and analytical study was performed on the whole nursing students of third semester in Ramsar Fatemeh Zahra nursing and midwifery faculty. Data was gathered with checklist and questionnaires with 15 questions related to the demographic and nursing satisfaction. Findings: Practical activities of nursing students in the communication were medium, with no relation for patient communication. Conclusion: According to the results, it could be suggested that knowledge and nursing satisfaction affects on the patient communication.